Reflective Narratives as a Type of Program Evaluation - Martínez Arbelaiz, Asunción (2017)
To show the efficiency of a given language program to interested stakeholders and to point to areas or aspects that require improvement are the two main objectives of any program evaluation. In this article, we describe the evaluation process of three Spanish as a second language programs in a study abroad context, where boundaries between learning inside and outside the classroom necessarily blur. Narrative inquiry is our methodological option because it allows us to understand the students experience in a holistic and nuanced manner.